Overview of Blood Glucose Levels in Diabetes Mellitus Patients at UPT Medan Health Laboratory in 2022 - Kelvin Sutirta Lase; Seri Rayani Bangun; Rica Vera Br Tarigan (Sean Institute, 2022)
This study aims to determine the distribution of blood glucose levels in patients with diabetes mellitus. This type of research design is descriptive analytic. The population is obtain from outpatient medical record data for diabetes mellitus patients for the last 3 months from January to March 2022 with a total of 63 people. The sample of this study amount to 63 people. Data collection is obtained through medical record data and the results of examination of blood glucose levels. The results of this study find that respondents with high fasting blood glucose levels are 54 people (85.9%), the age range that suffer the most from diabetes mellitus was the age range of 65-74 years. The increase in blood glucose is due to genetic factors, immunological factors, immunological factors, environment, age, and obesity.